Amphiregulin and Epidermal Hyperplasia: Amphiregulin Is Required to Maintain the Psoriatic Phenotype of Human Skin Grafts on Severe Combined Immunodeficient Mice - Bhagavathula, Narasimharao (American Society for Investigative Pathology, 2005)
Overexpression of amphiregulin has been shown to induce psoriasiform changes in the skin of transgenic mice shortly after birth. Therefore, amphiregulin has been suggested as a target for anti-psoriatic therapy. To test this theory, a humanized monoclonal antibody capable of neutralizing human amphiregulin was examined for anti-proliferative effects in the human skin-severe combined immunodeficient (SCID) mouse transplant model. The anti-amphiregulin antibody reduced epidermal thickness of transplanted psoriatic skin and also inhibited the hyperplastic response that developed in nonpsoriatic skin after transplantation. The same antibody also suppressed keratinocyte proliferation in monolayer culture in a dose-dependent manner. Under the same conditions in which keratinocyte proliferation was inhibited, the antibody had little effect on proliferation of human dermal fibroblasts and no effect on type I procollagen production by these cells. Taken together, these data indicate an important role for amphiregulin in psoriatic hyperplasia and suggest that inhibition of amphiregulin activity could be an efficacious therapeutic strategy for psoriasis. These data also suggest that the hyperplastic response occurring in nonpsoriatic human skin on transplantation to the SCID mouse is mediated, in large part, by amphiregulin.